Cryptocurrency Investment as a Marriage Dowry: An Analysis of Contemporary Islamic Family Law - Yusril Rahmatullah Sholeh; Saifullah; M. Aunul Hakim; Mutiara Nur Lailawati (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose - This study aims to examine the validity of using cryptocurrency as dowry in marriage based on contemporary Islamic law and positive law in Indonesia. The phenomenon of giving dowry in the form of digital assets such as Bitcoin, Ethereum, and USDT has sparked debate in contemporary Islamic family law. Methods - The research method used is the normative legal method with a conceptual approach. Data sources were obtained from legislation, religious fatwas, fiqh books, and scientific journals. Analysis was conducted using thematic and content analysis. Findings - The findings of this study indicate that cryptocurrency can be used as dowry in marriage, provided that there are clear underlying assets, such as Bitcoin, Ethereum, and USDT, which have economically measurable value. These assets can be accepted as dowry as long as both parties agree and they can be legally transferred. Conversely, if a type of cryptocurrency does not have a clear underlying asset, it is prohibited to use it as dowry in marriage. This demonstrates the adaptation and flexibility of Islamic family law to contemporary phenomena while remaining grounded in Islamic law. Research limitations - Limitations of the study in terms of empirical data. However, this study provides a conceptual contribution to the development of Islamic family law that is responsive to technological dynamics. Originality - This study makes a valuable contribution to the contemporary Islamic legal discourse in formulating legal guidelines regarding the use of digital assets.